DMT1 as a candidate for non-transferrin-bound iron uptake in the peripheral nervous system - Martínez Vivot, Rocío (2013)
Iron, either in its chelated form or as holotransferrin (hTf), prevents the dedifferentiation of Schwann cells (SC), cells responsible for the myelination of the peripheral nervous system (PNS). This dedifferentiation is promoted by serum deprivation through cAMP release, PKA activation, and CREB phosphorylation. Since iron elicits its effect in a transferrin (Tf)-free environment, in this work we postulate that non-transferrin-bound iron (NTBI) uptake must be involved. Divalent metal transporter 1(DMT1) has been widely described in literature as a key player in iron metabolism, but never before in the PNS context. The presence of DMT1 was demonstrated in nerve homogenate, isolated adult-rat myelin, and cultured SC by Western Blot (WB) analysis and confirmed through its colocalization with S-100β (SC marker) by immunocytochemical and immunohistochemical analyses. Furthermore, the existence of its mRNA was verified in sciatic nerve homogenate by RT-PCR and throughout SC maturational stages. Finally, we describe DMT1′s subcellular location in the plasma membrane by confocal microscopy of SC and WB of different subcellular fractions. These data allow us to suggest the participation of DMT1 as part of a Tf independent iron uptake mechanism in SC and lead us to postulate a crucial role for iron in SC maturation and, as a consequence, in PNS myelination.